Glutathione, carbohydrate and other metabolites of Larix olgensis A. Henry reponse to polyethylene glycol-simulated drought stress. - Lei Zhang (Public Library of Science (PLoS), 2021)
Drought stress in trees limits their growth, survival, and productivity and it negatively affects the afforestation survival rate. Our study focused on the molecular responses to drought stress in a coniferous species Larix olgensis A. Henry. Drought stress was simulated in one-year-old seedlings using 25% polyethylene glycol 6000. The drought stress response in these seedlings was assessed by analyzing select biochemical parameters, along with gene expression and metabolite profiles. The soluble protein content, peroxidase activity, and malondialdehyde content of L. olgensis were significantly changed during drought stress. Quantitative gene expression analysis identified a total of 8172 differentially expressed genes in seedlings processed after 24 h, 48 h, and 96 h of drought stress treatment. Compared with the gene expression profile of the untreated control, the number of up-regulated genes was higher than that of down-regulated genes, indicating that L. olgensis mainly responded to drought stress through positive regulation. Metabolite analysis of the control and stress-treated samples showed that under drought stress, the increased abundance of linoleic acid was the highest among up-regulated metabolites, which also included some saccharides. A combined analysis of the transcriptome and metabolome revealed that genes dominating the differential expression profile were involved in glutathione metabolism, galactose metabolism, and starch and sucrose metabolism. Moreover, the relative abundance of specific metabolites of these pathways was also altered. Thus, our results indicated that L. olgensis prevented free radical-induced damage through glutathione metabolism and responded to drought through sugar accumulation.